Relationship between Biopsychosocial Factors and Financial Risk Tolerance: An Empirical Study. (June 2016) - Kannadhasan, M; Aramvalarthan, S; Mitra, S K; Goyal, Vinay
Executive Summary: Financial risk tolerance (FRT) refers to the retail investors' willingness to accept the negative changes in the value of investment or an outcome that is adversely different from the expected one. Understanding and assessing FRT plays a crucial role in individual choices about wealth accumulation, portfolio allocation, and all other investment and finance-related decisions, and in achieving financial goals. An advisor has to accurately assess FRT for achieving his/her goal or investor's goal. Failure to do so leads to the choice of an investment option/portfolio which is inconsistent with one's FRT, resulting in investor disappointment, that is, unbearable loss to the client. Such a situation may adversely affect the client–advisor relationship. Measuring FRT is challenging as it is a multidimensional attitude. Besides, it is an elusive concept that appears to be influenced by a number of predisposing factors such as demographic, environmental, and psychosocial factors. This study aims to identify the factors that are related to risk tolerance from outside the financial services domain such as psychology, economics, and bio-sociology. It deals most specifically with the relationship between biopsychosocial factors and FRT. Those who are interested in assessing and predicting FRT can move closer to a theoretical account that blends psychological and economic insights and supplements the understanding of risk-taking attitudes and behaviour of retail investors. Such an understanding will help financial advisors, policy makers, and researchers in identifying the determinants of an individual's FRT to suggest the suitable investment alternatives to their clients. A single cross-sectional survey was conducted among 951 retail investors with various levels of investment experience through a structured questionnaire covering a variety of demographic factors. An analysis of the data collected through the questionnaire indicates that all the three factors—self-esteem, personality type, and sensation seeking—are positively related to FRT. This study adds to the extant literature on psychological determinants of FRT.